Economic Evaluation of Indigenous and Foreign Oil Palm Cultivation: A Case Study in Andhra Pradesh, India - P. Nandeeswara Rao; Sara Vijaya Laxmi; Aki Harshitha; Tandra Priyanka (Research Advances and Challenges in Agricultural Sciences Vol. 4, 2024)
This study investigates the agronomic performance, adaptability, economic viability, and associated challenges of indigenous and exotic oil palm varieties in Andhra Pradesh, India. Moreover this study analyses the differences between Indigenous and Exotic varieties of oil palm though the cultivations are growing both Indigenous and Exotic varieties, but prefer the Exotic varieties to cultivate in the future because of its higher production than the production of Indigenous varieties. This paper aims to provide valuable insights for sustainable cultivation practices. The comparative analysis includes growth parameters, yield potential, climate resilience, soil adaptation, and economic considerations. Through a carefully designed experimental setup, we assess the performance of selected varieties over time, considering environmental impacts, social considerations, and ethical aspects. India is the fourth leading oilseeds producing country in the world, next only to the USA, China, and Brazil, harvesting about 29 million tonnes of oilseeds per annum, grown in an area of nearly 27 Mha with an annual average yield of 1058 kg/ha. But As per the second advance estimates of fiscal year 2023, India produced 40 million metric tons of oilseeds. The 16.5 mt of edible oil imports in 2022-23 included palm (9.8 mt; from Indonesia, Malaysia and Thailand), soyabean (3.7 mt; from Argentina and Brazil) and sunflower (3 mt; from Russia, Ukraine and Argentina). The bulk of imports comprise crude oils.